2014
DOI: 10.1051/eas/1465005
|View full text |Cite
|
Sign up to set email alerts
|

How accurate are stellar ages based on stellar models?

Abstract: Abstract. Accurate and precise stellar ages are best determined for stars which are strongly observationally constrained, that is which are intrinsically oscillating. We review here the seismic diagnostics which are sensitive to stellar ages and provide some illustrating examples of seismically age-dated stars.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 117 publications
2
21
0
Order By: Relevance
“…We focus on evolved stars, and refer to Lebreton et al (2014), and references therein, for the case of main-sequence stars.…”
Section: From Precise To Accurate Stellar Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We focus on evolved stars, and refer to Lebreton et al (2014), and references therein, for the case of main-sequence stars.…”
Section: From Precise To Accurate Stellar Propertiesmentioning
confidence: 99%
“…With the advent of the Kepler (Borucki et al 2010) and CoRoT (Baglin et al 2006) space missions, time series measuring stellar variability of very-high quality have become widely available. Analysis of these time series can deliver precise estimates of stellar ages Lebreton et al 2014;Meibom et al 2015;Metcalfe et al 2015;Miglio et al 2013b;Silva Aguirre et al 2015) -a quantity critical for reconstructing the history of the Milky Way. With the re-purposed Kepler mission K2 (Howell et al 2014) currently capturing solar-like oscillations Stello et al 2015) in a number of different galactic directions, and the future missions of TESS (Ricker et al 2014) and PLATO (Rauer et al 2014) adding to this, ages for many thousands of stars in many different galactic distances and directions present an exciting possibility.…”
Section: Introductionmentioning
confidence: 99%
“…The ages determined with different stellar model can deviate by ∼10% for young stars and from 50% up to 100% for older stars (Lebreton et al 2014a). Only asteroseismology in combination with stellar evolution models can provide the age of main-sequence stars with an accuracy better than 10% (Lebreton et al 2014b). If the observed system is a cluster member, the age of the star can also be inferred from the age of the cluster.…”
Section: Introductionmentioning
confidence: 99%
“…However, they undergo phases with rapid change and/or experience pulsating episodes. Figure 1 in Lebreton et al (2014b), in these series, illustrates a Hertzprung-Russell diagram with different types of pulsation (a review on asteroseismology can be found in Cunha et al 2007). As a matter of fact, helioseismology has been a terrific tool to understand the internal structure of the Sun.…”
Section: Asteroseismologymentioning
confidence: 99%
“…Eventually CHEOPS, TESS and PLATO will add new information. Lebreton et al (2014b) discussed in depth asteroseismology and its application to the age-dating. We would like to emphasize few issues here, related to exoplanetary studies (see also subsection 3.6.1).…”
Section: Asteroseismologymentioning
confidence: 99%